Design method of high toughness grouting material

CN123017276APending Publication Date: 2026-10-30CHINA UNIV OF MINING & TECH (BEIJING) +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610863071.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-15
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]针对现有技术存在的不足,本发明的目的是提供一种高强韧性注浆材料设计方法,以解决或缓解上述现有技术中存在的问题

Benefits of technology

通过室内试验测试材料及破碎煤岩体加固体的力学性能,测试材料基本力学性能、可注性和加固效果并确定可注性指标作为材料设计参考标准;提出现场注浆方法,利用特制注浆加固装备,开展现场注浆测试,获取新型注浆材料现场注浆效果,并对注浆效果进行评价,反馈优化材料,形成高强韧性注浆材料配比的优化方法。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017276A_ABST
    Figure CN123017276A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of grouting material parameter optimization, and specifically discloses a high-strength and high-toughness grouting material design method, which comprises the following steps: mixing component A and component B at different proportions to obtain mixed slurry, testing the performance of the mixed slurry, and determining the optimal proportion of component A and component B; performing on-site grouting reinforcement testing and core testing before and after surrounding rock reinforcement according to the optimal proportion to calculate the on-site surrounding rock strength improvement rate; when the grouting reinforcement radius does not reach the material diffusion effect design standard, adjusting the proportion of polyether polyol and retarder in component A to increase the material fluidity and initial setting time; when the on-site surrounding rock strength improvement rate does not reach the broken rock mass reinforcement effect design standard, adjusting the proportion of polyphenyl polymethylene polyisocyanate in component B to improve the strength of the grouting material; and until the high-strength and high-toughness grouting material meets the design requirements. The application solves the problem that it is difficult to match the two-component high-polymer grouting material with the object to be grouted and reinforced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of grouting material parameter optimization technology, and in particular to a design method for high-strength and tough grouting materials. Background Technology

[0002] The statements herein provide only background information in relation to this invention and do not necessarily constitute prior art.

[0003] Grouting reinforcement technology improves the integrity and strength of rock masses through borehole grouting. It is a simple and low-cost process that effectively repairs roadways with loose surrounding rock. Polyurethane grouting technology involves injecting a two-component polymer material into fractured rock masses. After mixing, the material forms a solid that fills voids and reinforces the rock mass. However, current technologies lack a systematic and guiding method for optimizing the component ratios of polymer grouting reinforcement. This makes it difficult to achieve a good match between the two-component polymer grouting material and the object to be reinforced, thus hindering the effective exertion of the reinforcement performance of the two-component polymer. Summary of the Invention

[0004] In view of the shortcomings of the existing technology, the purpose of this invention is to provide a design method for high-strength and tough grouting materials to solve or alleviate the problems existing in the above-mentioned existing technology.

[0005] To achieve the above objectives, the present invention is implemented through the following technical solution: A design method for a high-strength and high-toughness grouting material includes the following steps: The high-strength and tough grouting material contains polyether polyol and retarder in component A, and polyphenyl polymethylene polyisocyanate in component B. Component A and component B are mixed in different proportions to obtain mixed slurry. The performance of the mixed slurry is tested to determine the optimal ratio of component A and component B. After mixing components A and B in the optimal ratio, on-site grouting reinforcement test and core sampling test before and after surrounding rock reinforcement were carried out. The integrity of the surrounding rock after reinforcement was determined based on the block structure and interlayer bonding state, so as to calculate the on-site surrounding rock strength improvement rate. When the grouting reinforcement radius does not meet the design standard for material diffusion effect, adjust the proportion of polyether polyol and retarder in component A to increase material fluidity and initial setting time. When the strength improvement rate of the surrounding rock at the site does not reach the design standard for the reinforcement effect of the fractured rock mass, adjust the proportion of polyphenyl polymethylene polyisocyanate in component B to increase the strength of the grouting material; Repeat the above steps until the high-strength and tough grouting material meets the design requirements.

[0006] In some embodiments, both component A and component B include a flame retardant.

[0007] In some embodiments, when determining the optimal ratio of component A and component B, the tested performance includes the injectability of the mixed slurry, the curing time, and the compressive and tensile strength of the specimens prepared from the mixed slurry.

[0008] Preferably, before testing injectability, the method further includes a step of using a rheometer to test the flowability and initial setting time of the mixed slurry to determine the injectability of the mixed slurry.

[0009] Preferably, the specimen for compressive strength testing is a standard cylindrical specimen with a height of 100 mm and a diameter of 50 mm; the size of the specimen for tensile strength testing should conform to relevant standards or testing requirements. For example, GB / T 528-2009 "Determination of Tensile Stress-Strain Properties of Vulcanized Rubber or Thermoplastic Rubber" specifies the specific dimensions and requirements of dumbbell-shaped specimens. The specimen can be made with a minimum total length of 100 mm, an end width of 20 mm, a narrow part length of 20 mm, a narrow part width of 5 mm, an outer transition radius of 11 mm, and an inner transition radius of 25 mm.

[0010] Preferably, the formula for the injectability index is as follows: (1); (2); (3); (4); In formulas (1)-(4), M is the slurry diffusion reduction rate index; t is the temperature compensation coefficient; m1 is the flow efficiency of the slurry in the material performance test; m2 is the diffusion efficiency of the slurry in the material grouting reinforcement test of fractured coal and rock mass. U represents the compressive strength performance index; U1 represents the compressive strength of intact rock; U2 represents the compressive strength of the grouting solidified rock. L represents the tensile strength index; L1 represents the tensile strength of intact rock; L2 represents the tensile strength of the grouting solidified body. LI is the injectability index, α, β, and γ are weighting coefficients, and T is the gelation time.

[0011] In some embodiments, the method for on-site grouting reinforcement testing includes the following steps: mixing component A and component B in the optimal ratio to obtain a mixed grout; Select grouting points and excavate grouting holes. The depth of the grouting holes should be 1 / 3 to 1 / 2 of the required reinforcement depth. The obtained mixed slurry is then pumped into the fractured surrounding rock for pressure grouting. Grouting is completed when the grouting pressure increases.

[0012] Preferably, the grouting device for pumping the mixed slurry into the fractured surrounding rock includes a component A storage container, a component B storage container, a pressure pump, a first slurry guide pipe, a second slurry guide pipe, and a slurry mixing tap; The inlet of the pressurizing pump is connected to the storage containers for component A and component B, respectively. The outlet of the pressurizing pump is connected to the inlet of the slurry mixing tap through the first slurry guide pipe and the second slurry guide pipe, respectively. The outlet of the slurry mixing tap is connected to the grouting pipe.

[0013] More preferably, the ends of the first slurry guide pipe and the second slurry guide pipe are connected and then connected to the slurry mixing tap.

[0014] In some embodiments, in the high-strength and toughness grouting material, component A, by mass parts, consists of the following components: 60-80 parts of polyether polyol; 10-20 parts of flame retardant; and 20-30 parts of retarder. Component B, by mass, consists of the following components: 80-90 parts of polyphenyl polymethylene polyisocyanate and 10-20 parts of flame retardant.

[0015] The beneficial effects achieved by one or more embodiments of the present invention described above are as follows: The mechanical properties of the materials and the reinforced fractured coal and rock mass were tested through indoor experiments. The basic mechanical properties, injectability, and reinforcement effect of the materials were tested, and the injectability index was determined as a reference standard for material design. An on-site grouting method was proposed. On-site grouting tests were carried out using specially designed grouting reinforcement equipment to obtain the on-site grouting effect of the new grouting materials. The grouting effect was evaluated, and feedback was used to optimize the materials and form an optimized method for the proportion of high-strength and tough grouting materials. Attached Figure Description

[0016] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.

[0017] Figure 1 This is a technical roadmap for the design method of high-strength and tough grouting materials provided in the embodiments of the present invention; Figure 2 This is a schematic diagram of the on-site grouting equipment for high-strength and tough grouting materials according to an embodiment of the present invention.

[0018] Among them, 1-container valve; 2-component A storage container; 3-slurry pressure monitor; 4-slurry mixing tap; 5-slurry pressure monitor; 6-first slurry guide pipe; 7-pressurization pump. Detailed Implementation

[0019] It should be noted that the following detailed description is illustrative and intended to provide further explanation of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0020] The present invention will be further described below with reference to the embodiments.

[0021] The high-strength and tough grouting material design method provided in this invention can be applied to the field of polymer material grouting reinforcement in underground engineering.

[0022] The two-component polymer grouting material is a polyurethane polymer material, including component A and component B used in combination. Component A is a colorless or light yellow liquid, and its main components are polyether polyol: 60%-80%, flame retardant: 10%-20%, and retarder: 20-30%, with the sum of the above components being 100%. Component B is a brownish-yellow clear organic mixture, and its main components are polyphenyl polymethylene polyisocyanate 80%-90% and flame retardant 10%-20%.

[0023] like Figure 1 As shown, the design method for high-strength and toughness grouting materials includes: experiments on the components and proportions of high-strength and toughness grouting materials; determination of the optimal material ratio for components A and B; performance testing of high-strength and toughness grouting materials; reinforcement effect standards under the optimal ratio; reinforcement tests on fractured coal and rock masses; design standards for material diffusion effects and fractured rock mass reinforcement effects, to provide feedback and optimize the optimal ratio of components A and B; material injectability indicators; field testing of high-strength and toughness grouting materials; field grouting reinforcement methods and core sampling tests of the reinforced surrounding rock, to provide feedback and optimize the materials and grouting methods.

[0024] Specifically, the design method for high-strength and tough grouting materials includes the following steps: (1) Conduct tests on the composition and configuration ratio of high-strength and tough grouting materials, prepare solutions of component A and component B with different ratios, test the material reaction effect and basic mechanical properties and injectability of the material, and determine the optimal material ratio; (2) Conduct grouting reinforcement tests on fractured coal and rock masses using high-strength and tough grouting materials, test the mechanical properties of the reinforced fractured coal and rock masses, test the reinforcement effect of the materials, and provide feedback to optimize the material composition of component A and component B, while determining the injectability index; (3) Propose on-site grouting methods, use grouting reinforcement equipment to carry out on-site grouting tests, obtain the on-site grouting effect of new grouting materials, evaluate the grouting effect, and provide feedback to optimize materials and grouting reinforcement methods, so as to form high-strength flexible grouting materials and application methods.

[0025] Figure 2This is a schematic diagram of the structure of a field grouting equipment for high-strength and tough grouting materials. The grouting equipment is a mixed grouting equipment, which consists of a grout storage system, a pressure pushing system, and a grout mixing and transmission system. The grout storage system consists of a component A storage container 2, a component B storage container, and a container valve 1. The pressure pushing system consists of a pressure pump 7 and a grout pressure monitor 3. The grout mixing and transmission system consists of a grout mixing tap 4, a grout pressure monitor 5, and a first grout guide pipe 6.

[0026] The inlet of the pressurizing pump 7 is connected to both the component A storage container 2 and the component B storage container. The outlet of the pressurizing pump 7 is connected to the inlet of the slurry mixing nozzle 4 via the first slurry guide pipe 6 and the second slurry guide pipe. The outlet of the slurry mixing nozzle 4 is connected to the grouting pipe. The ends of the first slurry guide pipe 6 and the second slurry guide pipe are connected to the slurry mixing nozzle 4.

[0027] The test of the composition and formulation ratio of high-strength and tough grouting materials includes the following steps: (1) Set up test control groups of grouting materials with different proportions of component A and component B. Mix the two groups of liquids in different proportions to obtain mixed grout. Use a rheometer to test the material fluidity and initial setting time to determine the injectability of the mixed grout. (2) Pour the mixed slurry prepared in different proportions into the mold to make a standard cylindrical specimen with a height of 100 mm and a diameter of 50 mm for compressive strength testing, and make a standard cylindrical specimen with a height of 50 mm and a diameter of 50 mm for tensile strength testing. (3) Conduct compressive and tensile tests on the materials under different curing times, further analyze the reactivity of the mixed grout, determine the optimal ratio of component A and component B based on the compressive and tensile properties of the test specimens and the curing time, and determine the reinforcement effect standard of component A and component B under the optimal ratio. The reinforcement effect standard is established by the strength of the high-strength and tough grouting material and the safety strength of the surrounding rock under the optimal ratio. The safety strength of the surrounding rock is determined by testing based on the on-site surrounding rock conditions or by numerical methods.

[0028] The test method for grouting reinforcement of fractured coal and rock masses includes the following steps: (1) The intact rock mass was made into standard test blocks, and its compressive strength and tensile strength were determined using a universal testing machine; (2) Screen the crushed rock masses with different particle sizes, use the prepared materials to grout and reinforce the crushed coal and rock masses, test the diffusion range and gelation time of the grout, and obtain the grout diffusion efficiency; (3) After the specimen is grouted, it is naturally cured indoors for 1 hour and then demolded. After being cured at room temperature for 1 day, the compressive strength and tensile strength of the solidified body are tested to obtain the strength change rate of the solidified body. (4) Compare the obtained compressive strength, tensile strength and grout diffusion efficiency with the reinforcement effect standard. If the grout diffusion efficiency is lower than the standard or the material strength is lower than the standard, the material composition ratio of component A and component B shall be re-optimized to complete the reinforcement effect evaluation and feedback. (5) Based on the results of the material injectability test, establish a material diffusion effect design standard. The diffusion effect design standard is established by referring to the slurry diffusion efficiency obtained from the injectability test and the required depth of the reinforcement ring for the target application roadway surrounding rock. The required depth of the reinforcement ring for the target application roadway surrounding rock is determined by field testing and numerical methods. A reinforcement effect design standard for fractured rock mass is proposed based on the strength change rate of the reinforced body. The reinforcement effect design standard for fractured rock mass is a reinforcement effect standard value determined by referring to the strength change rate of the reinforced body and the required safety strength of the target application roadway surrounding rock. The required safety strength of the target application roadway surrounding rock is determined by field testing and numerical methods.

[0029] The injectability of the high-strength and toughness grouting material is determined by several factors. First, the material should have a certain setting time to allow for long-distance transport. Second, it should possess strong fluidity to penetrate into fissures. Third, the curing time must meet the expected penetration depth. The injectability indicators, including grout diffusion reduction rate, compressive strength, and tensile strength, are used to determine whether a material is injectable.

[0030] The injectability indicators include the grout diffusion reduction ratio, compressive strength, and tensile strength. Grouting cannot be performed if the grout diffusion reduction ratio exceeds the specified index, or if the strength of the grouting material after reinforcement and curing does not meet the compressive or tensile strength indicators. Grouting can proceed smoothly if the grout diffusion reduction ratio is less than or equal to the specified index, or if the strength of the grouting material after reinforcement and curing meets the compressive or tensile strength indicators.

[0031] The formula for the slurry diffusion reduction rate index is as follows: ; In the formula, t is the temperature compensation coefficient, m1 is the flow efficiency of the grout used in the material performance test, and m2 is the diffusion efficiency of the grout used in the material grouting and reinforcement test of fractured coal and rock masses. This formula represents the rate of decrease in the flowability of the grouting material in rock fractures at different grouting temperatures relative to the flowability of pure grout.

[0032] The formula for the compressive strength performance index is as follows: ; In the formula, U1 is the compressive strength of intact rock, and U2 is the compressive strength of the grout-reinforced solid. This formula represents the effect of grouting on strengthening the compressive strength of fractured surrounding rock.

[0033] The formula for the tensile performance index is as follows: ; In the formula, L1 is the tensile strength of the intact rock, and L2 is the tensile strength of the grout-reinforced solid. This formula represents the effect of grouting on strengthening the tensile properties of fractured surrounding rock.

[0034] The formula for the weighted analysis of the regression coefficients of the injectability index is as follows: ; In the formula, LI represents the injectability index, α, β, and γ are weighting coefficients, T is the gelation time, M is the grout diffusion reduction rate index, L is the tensile strength index, and U is the compressive strength index. The weighting coefficients are determined using objective weighting methods, such as the coefficient of variation method, entropy method, CRITIC method, regression analysis, and structural equation modeling, based on the relationships between the original data. The original data comes from experiments or numerical simulations. This formula represents the range of grout diffusion within the gelation time of the grouting material and the strength of the resulting reinforced zone.

[0035] Injectability indicators are related to the material diffusion rate and material strength. The polyether polyol content in component A affects the material's fluidity, while the retarder content affects the material's setting time. When the slurry diffusion reduction rate exceeds the slurry diffusion reduction rate index, it indicates that the slurry's diffusion rate in the surrounding rock is too slow. Adjusting the proportion of polyether polyol in component A increases the material's fluidity, while simultaneously adjusting the proportion of retarder in component A increases the time required for the material to solidify from injection. The polyphenylene polymethylene polyisocyanate content in component B affects the material's strength. When the strength of the grouting material after curing does not reach the compressive and tensile strength indexes, adjusting the proportion of polyphenylene polymethylene polyisocyanate in component B improves the material's strength.

[0036] The experiment was conducted again based on the improved proportions until the design requirements were met, thus completing the optimization of the high-strength and tough grouting material.

[0037] Field tests of high-strength and tough grouting materials, including field grouting reinforcement tests, core sampling tests before and after surrounding rock reinforcement, and the formation of reinforcement evaluation methods.

[0038] The on-site grouting reinforcement method includes the following steps: (1) Select the on-site roadway grouting test section, prepare high-strength and tough grouting material components A and B, and store them separately; (2) Select grouting points and use a drilling rig to excavate grouting holes. The depth of the excavated grouting holes is determined according to the required reinforcement depth, which is 1 / 2 of the required reinforcement depth. Then, use on-site grouting equipment to mix the two components at a volume ratio of 1:1 and pump them into the fractured surrounding rock. Under the action of grouting pressure, the two components are further fully mixed and penetrate into the surrounding rock fissures. During the grouting process, monitor the changes in grouting pressure in real time. Take the moment when the grouting pressure increases as the moment when grouting is completed and stop grouting. After solidification reaction, the rock mass forms a reinforced zone.

[0039] The high-strength and tough grouting material field grouting equipment is a mixed grouting equipment, which consists of a grout storage system, a pressure pushing system, and a grout mixing and transmission system, and can achieve full mixing and pressurized release of components A and B.

[0040] The core sampling test before and after surrounding rock reinforcement includes two parts: (1) Before reinforcement, core tests were conducted on the surrounding rock of the test section to obtain the strength of the surrounding rock before reinforcement, and the integrity of the surrounding rock before reinforcement was determined based on the blocky structure and interlayer bonding state. (2) After the reinforcement material has fully cured, core samples are taken from the reinforced surrounding rock of the test section to test the reinforcement effect of the rock sample, obtain the strength of the reinforced surrounding rock, and determine the integrity of the reinforced surrounding rock according to the block structure and interlayer bonding state, and calculate the strength improvement rate of the surrounding rock in the field test.

[0041] The formula for calculating the strength improvement rate of the surrounding rock in the field test is as follows: ; In the formula, △S is the strength improvement rate of the surrounding rock in the field test, S2 is the strength of the surrounding rock after reinforcement, and S1 is the strength of the surrounding rock before reinforcement.

[0042] The reinforcement effect evaluation and feedback method involves evaluating and providing feedback based on the improvement in the integrity of the surrounding rock and the increase in its strength. The integrity of the surrounding rock is determined according to the "Technical Specification for Rock and Soil Anchors and Shotcrete Support Engineering," and is graded based on indicators such as rock mass integrity and rock strength. Changes in the grading of the surrounding rock before and after reinforcement represent the improvement in its integrity. When the grouting reinforcement radius of the tested surrounding rock does not meet the design standard for material diffusion, the proportion of polyether polyol in material A is adjusted to increase its fluidity. Simultaneously, the proportion of retarder in material A is adjusted to increase the time required for the material to solidify from injection. When the strength improvement rate of the reinforced surrounding rock in the test did not meet the design standard for the reinforcement effect of fractured rock mass, the proportion of polyphenylene polymethylene polyisocyanate in material B was adjusted to improve the material strength. The test was repeated according to the improved mix ratio until the design requirements were met, thus completing the optimization of the high-strength and toughness grouting material.

[0043] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A design method for high-strength and toughness grouting materials, characterized in that: Material design includes the following steps: The high-strength and tough grouting material contains polyether polyol and retarder in component A, and polyphenyl polymethylene polyisocyanate in component B. Component A and component B are mixed in different proportions to obtain mixed slurry. The performance of the mixed slurry is tested to determine the optimal ratio of component A and component B. After mixing components A and B in the optimal ratio, on-site grouting reinforcement test and core sampling test before and after surrounding rock reinforcement were carried out. The integrity of the surrounding rock after reinforcement was determined based on the block structure and interlayer bonding state, so as to calculate the on-site surrounding rock strength improvement rate. When the grouting reinforcement radius does not meet the design standard for material diffusion effect, adjust the proportion of polyether polyol and retarder in component A to increase material fluidity and initial setting time. When the strength improvement rate of the surrounding rock at the site does not reach the design standard for the reinforcement effect of the fractured rock mass, adjust the proportion of polyphenyl polymethylene polyisocyanate in component B to increase the strength of the grouting material; Repeat the above steps until the high-strength and tough grouting material meets the design requirements.

2. The design method for high-strength and tough grouting materials according to claim 1, characterized in that: Both component A and component B contain flame retardants.

3. The design method for high-strength and tough grouting materials according to claim 1, characterized in that: When determining the optimal ratio of component A and component B, the tested properties include the injectability of the mixed slurry, the curing time, and the compressive and tensile strength of the specimens prepared from the mixed slurry.

4. The design method for high-strength and toughness grouting materials according to claim 3, characterized in that: Prior to testing injectability, the process includes using a rheometer to test the flowability and initial setting time of the mixed slurry to determine its injectability.

5. The design method for high-strength and toughness grouting materials according to claim 3, characterized in that: The formula for calculating the strength improvement rate of the surrounding rock in the field test is as follows: ; In the formula, △S is the strength improvement rate of the surrounding rock in the field test, S2 is the strength of the surrounding rock after reinforcement, and S1 is the strength of the surrounding rock before reinforcement.

6. The design method for high-strength and toughness grouting materials according to claim 3, characterized in that: The formula for the injectability index is as follows: (1); (2); (3); (4); In formulas (1)-(4), M is the slurry diffusion reduction rate index; t is the temperature compensation coefficient; m1 is the flow efficiency of the slurry in the material performance test; m2 is the diffusion efficiency of the slurry in the material grouting reinforcement test of fractured coal and rock mass. U represents the compressive strength performance index; U1 represents the compressive strength of intact rock; U2 represents the compressive strength of the grouting solidified rock. L represents the tensile strength index; L1 represents the tensile strength of intact rock; L2 represents the tensile strength of the grouting solidified body. LI is the injectability index, α, β, and γ are weighting coefficients, and T is the gelation time.

7. The design method for high-strength and tough grouting materials according to claim 1, characterized in that: The method for on-site grouting reinforcement testing includes the following steps: Mix component A and component B in the optimal ratio to obtain a mixed slurry; Select grouting points and excavate grouting holes. The depth of the grouting holes should be 1 / 3 to 1 / 2 of the required reinforcement depth. The obtained mixed slurry is then pumped into the fractured surrounding rock for pressure grouting. Grouting is completed when the grouting pressure increases.

8. The design method for high-strength and tough grouting materials according to claim 7, characterized in that: The grouting device for pumping mixed slurry into fractured surrounding rock includes a component A storage container, a component B storage container, a pressurizing pump, a first slurry guide pipe, a second slurry guide pipe, and a slurry mixing tap. The inlet of the pressurizing pump is connected to the storage containers for component A and component B, respectively. The outlet of the pressurizing pump is connected to the inlet of the slurry mixing tap through the first slurry guide pipe and the second slurry guide pipe, respectively. The outlet of the slurry mixing tap is connected to the grouting pipe.

9. The design method for high-strength and toughness grouting materials according to claim 8, characterized in that: The ends of the first slurry guide pipe and the second slurry guide pipe are connected and then connected to the slurry mixing tap to fully mix the two slurries flowing in through the two guide pipes.

10. The design method for high-strength and tough grouting materials according to claim 1, characterized in that: In the high-strength and tough grouting material, component A, by mass parts, consists of the following components: 60-80 parts of polyether polyol; 10-20 parts of flame retardant; and 20-30 parts of retarder. Component B, by mass, consists of the following components: 80-90 parts of polyphenyl polymethylene polyisocyanate and 10-20 parts of flame retardant.